Pengaruh Literasi Kewirausahaan dan Karakter Wirausaha terhadap Keberhasilan Usaha Kecil - Irta Yani; Muhammad Rakib; Agus Syam (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2020)
This study aims to determine the effect of entrepreneurial literacy and entrepreneurial character on the success of small-scale business studies on culinary entrepreneurs in Enrekang district. This research is categorized as a quantitative descriptive study with a correlation approach. The population in this study were 100 entrepreneurs, and obtained a sample of 80 entrepreneurs who were culinary entrepreneurs in Enrekang district. Data collection was carried out by means of observation, documentation and questionnaire techniques. The analysis technique used is multiple linear regression. The results of this study indicate that entrepreneurial literacy (X1) and entrepreneurial character (X2) have a positive and significant effect on the success of small business (Y) culinary entrepreneurs in Enrekang district both partially and simultaneously. In this study, the most dominant variable influencing is the entrepreneurial character variable because it has a higher regression coefficient value than the entrepreneurial literacy regression coefficient value.